Tratamiento contable del activo biológico: planta productora, enmienda a NIC 41. - Caiminagua Iñaguazo, Marjorie Cecibel; Carrión Rodríguez, Kelly Stephanny (My University, 2021)
This paper demonstrates the accounting changes applied to agricultural activity, based on the International Accounting Standard IAS 41 Agriculture, which is the main regulation governing the accounting treatment of biological assets, however, with the reform called Amendment to IAS 41, The scope of IAS 41 and IAS 16 Plant and Equipment Ownership is modified, focusing on the accounting treatment of producing plants. The present study consists of a comparison of the effects that have occurred in the agricultural sector, following the reforms applicable to the accounting process of producing or supporting plants. The research is descriptive based on the revision of regulations among other bibliographic sources. The results show the main changes in regulations focused on the scope, recognition, and measurement of biological assets. Each process of the development of the production plant has a different accounting, demonstrating the applicability of each regulation according to the type of crop either short or permanent cycle.
El presente trabajo demuestra los cambios contables aplicados a la actividad agrícola, sustentados en la Norma Internacional del Contabilidad NIC 41 Agricultura, la cual es la normativa principal que rige el tratamiento contable de los activos biológicos, sin embargo, con la reforma denominada Enmienda a NIC 41, se modifica el alcance de la NIC 41 y NIC 16 Propiedad Planta y Equipo, centrándose en el tratamiento contable de las Plantas Productoras. El presente estudio consiste en realizar una comparación de los efectos que se han dado en el sector agrícola, a raíz de las reformas aplicables al proceso de contabilización de las plantas productoras o portadoras. La investigación es descriptiva basada en la revisión de normativas entre otras fuentes bibliográficas. Los resultados muestran los principales cambios en las normativas enfocadas en el alcance, reconocimiento y medición del activo biológico. Cada proceso del desarrollo de la planta productora tiene una diferente contabilización, demostrando la aplicabilidad de cada normativa de acuerdo al tipo de cultivo ya sea ciclo corto o permanente.
Keywords: ACTIVOS BIOLÓGICOS; PLANTA PRODUCTORA